Application of Music Therapy to Reduce Anxiety of Non-Hemorrhagic Stroke (NHS) Patients - Yulianingsih, Devi; Karlina, Nonok; Muadi, Muadi (Nurul Jadid University, Probolinggo, East Java, Indonesia, 2025)
Ischemic stroke or non-hemorrhagic stroke (SNH) is a condition where there is a blockage of blood vessels that causes blood flow to the brain to partially or completely stop. This final scientific work aims to assess the effectiveness of music therapy in non-hemorrhagic stroke (SNH) patients with anxiety nursing problems. The method applied in the preparation of this final scientific work is a single case study method. The subject in this case study involves one client with a case of non-hemorrhagic stroke (SNH) and has an anxiety problem who is undergoing treatment. Data collection using interview techniques, observation and documentation. The nursing care process for clients is carried out for 3 days, and the results of the assessment are obtained, namely the stiff body on the left so that the patient experiences anxiety (anxiety) due to the conditions experienced. The intervention provided is the reduction of anxiety combined with the application of EBN, namely music therapy which is implemented for 15 minutes for 1 time in 3 days. Based on the evaluation results, it was found that on the third day the nursing problem of anxiety had been resolved with objective data the patient looked calm. Furthermore, it can be concluded that music therapy can reduce the level of anxiety in non-hemorrhagic stroke (SNH) patients. Music therapy interventions can be included as part of the nursing SOP or supporting therapy.